2006
DOI: 10.1063/1.2359627
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of simulated and experimentally obtained nonuniformity in thermal and electrical properties of conducting films

Abstract: The effect of localized microwave absorption in conducting thin films had been simulated using a heat diffusion model to quantitatively evaluate the electrical voltage maps obtained recently using a near-field scanning microwave microprobe (NSMM) in combination with the I-V characterization. In the experiment, the focused microwave emitted from the NSMM at a sample spot of dimension comparable to the NSMM tip dimension changes the local resistivity of the sample via microwave heating. By measuring the voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results calculated by Turja Nandy further illustrate that the carrier concentration of Gr exhibits a positive temperature dependence [ 34 ]. Based on these results, it can be hypothesized that the transient thermogenesis (~404 K) induced when the high-frequency signal emitted by the tip of the needle interacts with the Gr during the SMIM test process [ 33 , 35 ] results in an elevation of Gr Fermi energy level, leading to the increasing of carrier concentration, as shown in Figure 4 b. Considering the significantly higher carrier mobility of Gr and the notably increased carrier concentration of Gr at high frequencies, it can be concluded that based on the classic Drude model.…”
Section: Resultsmentioning
confidence: 99%
“…The results calculated by Turja Nandy further illustrate that the carrier concentration of Gr exhibits a positive temperature dependence [ 34 ]. Based on these results, it can be hypothesized that the transient thermogenesis (~404 K) induced when the high-frequency signal emitted by the tip of the needle interacts with the Gr during the SMIM test process [ 33 , 35 ] results in an elevation of Gr Fermi energy level, leading to the increasing of carrier concentration, as shown in Figure 4 b. Considering the significantly higher carrier mobility of Gr and the notably increased carrier concentration of Gr at high frequencies, it can be concluded that based on the classic Drude model.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary work on the application of this technique on conducting silver thin films has been done previously [5] and supporting numerical simulations have also been carried out to gain a better understanding of the mechanism of heat absorption in films by microwave irradiation [6]. In this paper, we present results on applying this technique for imaging current-obstructing defects in YBCO thin films.…”
Section: Introductionmentioning
confidence: 96%